2014
DOI: 10.1167/iovs.14-15468
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Subclinical Visual Damage After Blast-Mediated TBI Enables Prevention of Chronic Visual Deficit by Treatment With P7C3-S243

Abstract: Provocative PERG testing serves as a noninvasive test in the living organism to identify early damage to the visual system, which may reflect corresponding damage in the brain that is not otherwise detectable by noninvasive means. This provides the basis for developing an earlier diagnostic test to identify patients at risk for developing chronic CNS and visual system damage after TBI at an earlier stage when treatments may be more effective in preventing these sequelae. In addition, treatment with the neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 33 publications
(49 reference statements)
4
91
0
Order By: Relevance
“…Others have also observed retinal signaling deficits by ERG in conjunction with retinal cell damage by histopathology in mouse models of blast wave exposure (Hines-Beard, 2012;Jiang, 2013;Mohan, 2013;Bricker-Anthony, 2014a, b;Dutca, 2014;Bricker-Anthony, 2015); but the injury is unrealistically catastrophic (e.g., optic nerve avulsion) or delayed in manifestation (e.g., several months) due to very poor simulation of the blast waves. For example, multiple studies have fired a high velocity air rifle directly at a mouse's cornea (Hines-Beard, 2012;Jiang 2013;Bricker-Anthony, 2014a, b;Dutca, 2014;Bricker-Anthony, 2015) and another put mice inside an uncontrolled air expansion blast chamber having an obscure end delivery pressure (Mohan, 2013). These studies misleadingly report results of air jet and not blast wave models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have also observed retinal signaling deficits by ERG in conjunction with retinal cell damage by histopathology in mouse models of blast wave exposure (Hines-Beard, 2012;Jiang, 2013;Mohan, 2013;Bricker-Anthony, 2014a, b;Dutca, 2014;Bricker-Anthony, 2015); but the injury is unrealistically catastrophic (e.g., optic nerve avulsion) or delayed in manifestation (e.g., several months) due to very poor simulation of the blast waves. For example, multiple studies have fired a high velocity air rifle directly at a mouse's cornea (Hines-Beard, 2012;Jiang 2013;Bricker-Anthony, 2014a, b;Dutca, 2014;Bricker-Anthony, 2015) and another put mice inside an uncontrolled air expansion blast chamber having an obscure end delivery pressure (Mohan, 2013). These studies misleadingly report results of air jet and not blast wave models.…”
Section: Discussionmentioning
confidence: 99%
“…only two animal studies have evaluat ed drugs (nicotinamide and p-adrenergic agonists) for blast induced neurotrauma to the eyes Oiang, 2013;Dutca, 2014).…”
Section: Electroretinography (Erg)mentioning
confidence: 99%
See 1 more Smart Citation
“…levels in the brain. To address this problem, we turned to the neuroprotective aminopropyl carbazole compound P7C3-A20, a small molecule that blocks neuronal cell death, [22][23][24][25][26][27][28] thereby increasing the magnitude of hippocampal neurogenesis. [29][30][31] Treatment of forebrain Ca v 1.2 cKO mice with P7C3-A20 restored normal survival of young hippocampal neurons (Fig.…”
mentioning
confidence: 99%
“…Indeed, the progressive nature of many forms of neuropsychiatric disease, including those linked to CACNA1C, is consistent with neurodegenerative processes that would be amenable to treatment with neuroprotective agents. 46 In this light, it is useful to note that P7C3 compounds have demonstrated protective efficacy in preclinical models of Parkinson disease, 24,[28][29] cognitive decline with aging, 31 amyotrophic lateral sclerosis, 23 traumatic brain injury, [25][26][27] peripheral nerve injury, 22 neurodegeneration-associated depression, 46 and now cell death associated with genetic susceptibility to mental illness. 17 It has recently been reported that P7C3 compounds enhance flux of the nicotinamide adenine dinucleotide (NAD) salvage pathway in normal mammalian cells, and also facilitate NAD recovery following doxorubicin exposure.…”
mentioning
confidence: 99%